Penambahan Gardu Distribusi Berdasarkan Pertumbuhan Beban Listrik Menggunakan GUI Matlab di Wilayah Tangerang - Adri Senen; Oktaria Handayani; Christine Widyastuti (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Distribution system development Planning is very important in line with the increasing need for electricity loads, attention must be paid to quality of power delivered to consumers. The addition of a distribution network will certainly result in an increase in the capacity and number of transformers and distribution substations. The addition of distribution substations was based on the selection of distribution transformer ratings based on the growth of their load. The distribution transformer loading is made at a maximum of 80% with distributed model. Distribution transformers addition calculation requires an approach to connect the total distribution transformers and distribution substations, namely the average result of the total distribution transformers divided by the total distribution substations, it requires quite complex calculations. To make planning for adding distribution substations easier, you can use the Matlab Graphical User Interface (GUI). With the Matlab GUI program, projections for adding substations can be done easily, quickly, and precisely, and can be applied to any region more accurately. Based on the results of the GUI simulation, it was found that the total additional transformer capacity for the Tangerang area was 1.6 MVA with the addition of 7 distribution substations.